...'Til we meet again [compact disc] : live - Jones, Norah, 1979-; Jones, Norah, 1979- (Blue Note Records, 2021)
Nearly 2 decades into her career, GRAMMY-winning artist Norah Jones is set to release her first live album, `Til We Meet Again. With performances from the US, France, Italy, Brazil & Argentina recorded between 2017-19. Spanning her entire career from her 2002 debut to her more recent singles "It Was You" and GRAMMY-nominated "I'll Be Gone." It closes with a cover of Soundgarden's "Black Hole Sun," a tribute to Chris Cornell recorded at the Fox Theatre just days after Cornell's death.